(untitled) (The Peerian Journal, 2022)
When improving the content of school education in physics using the problem type, the article describes the psychological components of a student’s cognitive activity, its namelessness, the need to know, the structure of mental abilities. Using the problematic type of questions in the lesson, the features, opportunities and tasks of directing a student to creative activity are widely covered.